Penerimaan Khalayak pada Tayangan Behind The Scene sebagai Materi Promosi Film 13 Bom di Jakarta - Jonathan, Enrian; Agung, I Putu Suhada (Universitas Dinamika, 2025)
Visinema Pictures produced the film 13 Bombs in Jakarta on a large scale and technically complex, so they have a claim that the film is the biggest action film in Indonesia that year. Visinema saw the scale of the film's production as one of the production value that could be offered, so they used behind-the-scenes footage as one of their main promotional materials. Promotion is one of the important stages in the film distribution stage in order to get maximum economic results from its screening. Good promotional parameters include cognitive, affective and conative responses produced by a person, according to the marketing management study hierarchy of effects model by Lavidge and Steiner (1960). This research focuses on audience acceptance of Visinema's film promotion strategy through behind-the-scenes shows. Qualitative research methods are used to discover new phenomena resulting from the screening of these shows as promotional material for films. One form of data collection in this research uses focused group discussions with ISI Surakarta Film and Television student participants, so that the acceptance of this form of promotion is known. The resulting responses serve as verification of interviews with publicists for the film 13 Bom in Jakarta as well as measuring the effectiveness of film promotional media for the film itself. Based on data analysis and drawing conclusions, the form of promotion carried out by Visinema through behind-the-scenes shows succeeded in achieving the ultimate goal for the majority of informants and was effective in creating awareness, knowledge, interest, and even the decision to watch the film. The results of the questionnaire showed that 75% of respondents stated that it was cognitively and affectively interesting.